Bin Picking Success Rate Depending on Sensor Sensitivity - Doležel, Petr; Pidanič, Jan; Zálabský, Tomáš; Dvořák, Miroslav (IEEE (Institute of Electrical and Electronics Engineers), 2019)
The goal of this contribution is to determine correlation between an applied sensor for object registration and the success rate of the bin-picking problem. In most applications of a bin picking problem in industry, the procedure consists of two consecutive steps. The first step provides an initial guess of both position and rotation angle of the object to be registered, while the second one improves the exact pose accuracy, as required in following tasks. The second step can be, among others, implemented by the Iterative Closest Point Algorithm (ICP). It is well known that the ICP algorithm is very sensitive to the initial guess of the position and rotation angle of the object. Another interesting feature, especially from the technician’s point of view, is the sensitivity of the ICP algorithm in relation to the applied sensor. Therefore, one particular bin picking application, involving complex irregular objects, is examined in this paper. Various kinds of sensors for 3D scene reconstruction are employed and, as a result of this contribution, a comprehensive set of relations between sensor quality and the ICP algorithm sensitivity is formulated.
Úspěšnost řešení bin picking problému v závislosti na citlivosti senzoru
Keywords: Bin Picking; Point Clouds; Pose Estimation; Robotic Arm; Bin Picking; bodové mračno; odhad polohy a natočení; robotické rameno